Flexible learning dimensions in higher education: aligning students’ and educators’ perspectives for more inclusive practices - El Galad, Asil; Betts, Dean Harvey; Campbell, Nicole (Frontiers in Education, 2024)
Driven by the rise of recent technologies and long-standing interest in accommodating diverse student needs, the demand for flexibility in higher education has intensified. Moreover, the COVID-19 pandemic has intensified studies investigating online learning effects, reflecting shifting preferences and demands in education. Although prior research recognizes diverse flexibility practices, a narrow focus on instructional delivery limits its potential. Bridging this gap requires re-envisioning flexible learning by involving students, educators, and institutions in the transformation process. Therefore, this study aims to investigate and compare students' and educators' perspectives and experiences of five dimensions of flexibility (deadlines, modality, assessment type, grading and weighting, and course correspondence). The study involves a quantitative and qualitative survey, composed of Likert scale and open-ended questions. The survey respondents were students (N=315) and educators (N=100) at XX University across different years and programs.The quantitative component reveals a general alignment between student and educator preferences across flexibility dimensions. Noteworthy preferences include collaborative deadline setting, non-timed and take-home assessments, and more frequent, lower-weighted tasks. Students' increased preference for hybrid learning, despite a general preference for in-person formats, underscores the value placed on flexibility and adaptability. Qualitative findings illuminate the broader implications of flexibility that can be organized into the following four themes: (1) flexibility humanizes teaching and learning, (2) flexibility recognizes diverse student populations, (3) flexibility provides broad accommodation and increases accessibility, and (4) flexibility can offer immediate relief but poses long-term consequences.In conclusion, this study emphasizes the multifaceted nature of flexibility in higher education, offering a nuanced understanding of the impact of flexibility on students, educators, and institutions, encouraging further exploration and evidence-based policy decisions. Beyond academia, the research suggests potential reshaping of the higher education landscape, positioning flexibility as a fundamental element to foster a more inclusive, supportive, and effective learning environment for both students and educators.